The Assessment Instrument of Mathematics Learning Outcomes Based on HOTS Toward Two-Dimensional Geometry Topic - I Gede Wahyu Suwela Antara; I Komang Sudarma; I.Ketut Dibia (Universitas Pendidikan Ganesha, 2020)
This study aims to (1) developing a mathematics assessment instrument based on Higher Order Thinking Skills (HOTS); and describe the quality of the instrument. This study was a research and development study adapting 4D model from Thiagarajan. The model including the following steps : (1) define, (2) design, (3) develop, and (4) desseminate. Due to limited of time, this research was only carried out until the developing step.The result shows that the instrument that consists of 18 essay test item are valid and appropriate to be used. The instrumen’s reliability coefficients are 0.659 (High). The instrument has the average of item discrimination 0.44 (Very Good) and the average of item difficulty of the instrument are 0.584 (Medium). The conclusion is the assessment instrument is feasibel being as an assessment instrumen to measure the high order thinking skill toward two-dimentional geometry topic.